Factors associated with pregnancy and induced abortion among street-involved female adolescents in two Nigerian urban cities: a mixed-method study - Mary O. Obiyan; Atinuke O. Olaleye; Funmilola F. Oyinlola; Morenike O. Folayan (BMC, 2023)
Abstract Objectives This study determined the correlates of unwanted pregnancy and induced abortion among sexually active female street-involved adolescents (SIAs) aged 10-19 years in two urban cities in South-west, Nigeria. Methods The data for this study were extracted from a larger mixed-method survey dataset on the sexual and reproductive health (SRH) of 1505 street-involved young people aged 10 to 24 years. For the quantitative data, the explanatory variables were age, history of school attendance, employment status, religion, living arrangement and city of residence. The study outcomes were a history of pregnancy and a history of induced abortion of last pregnancy. Binomial regression analysis was performed to determine the association between the explanatory and outcome variables. For the qualitative data generated through focus group discussions and in-depth-interviews, inductive and deductive approaches were used in conducting a thematic analysis to explore the perspectives and experiences of SIA on pregnancy and induced abortion. Results Of the 424 female SIAs, 270 (63.7%) reported having had sex. Sixty-four (23.7%) respondents had a history of pregnancy, of which 38 (59.4%) gave a history of induced abortion of the last pregnancy. A history of school attendance significantly reduced the likelihood of being pregnant (AOR: 0.42, 95% C.I: 0.19-0.91), while 15-19-years-old SIAs who were pregnant were significantly less likely to abort (AOR: 0.13, 95% C.I: 0.02-0.77). Qualitative reports indicated that unintended pregnancy and induced abortion was a common experience among the sexually active SIAs. Many participants were aware of the methods of, and places to induce abortion. Conclusion A large proportion of SIAs are sexually active with a high incidence of unintended pregnancy and a high rate of unsafe abortion. Access of female SIAs to education can reduce the risk of unintended pregnancy. Attention needs to be paid to how SIAs can have access to contraception.